Controllable and high‐performance immobilized enzyme reactor: DNA‐directed immobilization of multienzyme in polyamidoamine dendrimer‐functionalized capillaries. Issue 5 (22nd January 2020) - Li, Mengqi; Shen, Hao; Zhou, Zixin; He, Wenting; Su, Ping; Song, Jiayi; Yang, Yi
Abstract: In recent years, CE‐integrated immobilized enzyme reactors (IMERs) for single‐enzyme immobilization have attracted considerable attention. However, there has been little research on multienzyme immobilization in CE. Here, we introduce a method for fabricating a CE‐integrated IMER, using DNA‐directed immobilization to fix glucose oxidase and horseradish peroxidase in the capillary, which had been functionalized with polyamidoamine dendrimer (PAMAM). Owing to the reversibility of DNA hybridization, the reactor is capable of dynamic immobilization. Moreover, by introducing the PAMAM, the loading capacity of the IMER is greatly enhanced, and the PAMAM can spontaneously form complexes with DNA and then contribute to the efficiency and stability of the reactor. After 25 days storage, the prepared IMER ultimately retained approximately 70% of its initial activity. We also used the IMER to detect glucose, and the favorable linearity was obtained over the concentration range of 0.78–12.5 mM, with an LOD of 0.39 mM, demonstrating that the CE‐integrated IMER can be applied to actual samples. We believe that this strategy can be extended to other multienzyme immobilization systems, and CE‐integrated IMERs are potentially useful in a wide range of biochemical research applications.